The evaluation of the National Learning Network - Caven-Atack , Andrew S. Thomas (Research in Learning Technology)
The National Learning Network (NLN) is part of a response to the expectation that the further education (FE) sector within England will grow steadily over the next three years to fulfil the Department for Employment and Education’s requirement to widen participation in this area of education. The NLN is just one of the initiatives aimed at (though not exclusive to) new students from non-traditional, disadvantaged and previously excluded groups, and is expected to bring the student population in FE to over four million. The Further Education Funding Council (FEFC) has noted that traditional FE learning paradigms are not suitable for this level of participation and that increased levels of information and learning technology (ILT) will need to be implemented to cope with these increased student numbers. DOI:10.1080/0968776000080304